1999
DOI: 10.1152/ajpcell.1999.276.1.c54
|View full text |Cite
|
Sign up to set email alerts
|

Differing temporal roles of Ca2+ and cAMP in nicotine-elicited elevation of tyrosine hydroxylase mRNA

Abstract: The involvement of cAMP- and Ca2+-mediated pathways in the activation of tyrosine hydroxylase (TH) gene expression by nicotine was examined in PC-12 cells. Extracellular Ca2+ and elevations in intracellular Ca2+ concentration ([Ca2+]i) were required for nicotine to increase TH mRNA. The nicotine-elicited rapid rise in [Ca2+]iwas inhibited by blockers of either L-type or N-type, and to a lesser extent P/Q-, but not T-type, voltage-gated Ca2+ channels. With continual nicotine treatment, [Ca2+]ireturned to basal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
64
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 39 publications
6
64
0
1
Order By: Relevance
“…Long-term treatment with nicotine increases the concentration of TH-mRNA and, consequently, TH-activity, both in vivo and in chromaffin cells [62] . This effect is calcium-dependent and mediated by protein kinase A (PKA) [63] . The nicotine-induced activation of expression of the gene encoding TH requires a prolonged increase in calcium concentration, and the activation of store-dependent calcium channels [63] and ERK/MAPK [64] .…”
Section: Instantaneous Effectsmentioning
confidence: 99%
“…Long-term treatment with nicotine increases the concentration of TH-mRNA and, consequently, TH-activity, both in vivo and in chromaffin cells [62] . This effect is calcium-dependent and mediated by protein kinase A (PKA) [63] . The nicotine-induced activation of expression of the gene encoding TH requires a prolonged increase in calcium concentration, and the activation of store-dependent calcium channels [63] and ERK/MAPK [64] .…”
Section: Instantaneous Effectsmentioning
confidence: 99%
“…We identified the signaling pathways, such as mitogen-activated protein kinase (MAPK), epidermal growth factor receptor (EGRF), phosphatidylinositol, to which these genes belong. The relevance of these pathways to nicotine administration was also assessed based on the available literature [52,16,32].…”
Section: Region-specific Expression Profiles In Response To Chronic Nmentioning
confidence: 99%
“…Nicotine also has been shown to elevate intracellular calcium levels upon activation of the store-operated calcium channels possibly by an increase in the D-myo-inositol 1,4,5-trisphosphate (Ins(1,4,5)P 3 ) production [16].In this study we identified a number of genes, such as profilin 1, Ins(1,4,5)P 3 3-kinase B, and PTEN, involved in Ins(1,4,5)P 3 turnover as well as intracellular calcium homeostasis, as potential modulators/targets of nicotine in rat brain. Profilin negatively regulates the phophoinositide signaling pathway by binding with phosphatidylinositol 4,5-bisphosphate (PIP2) and preventing the formation of Ins(1,4,5)P and diacylglycerol via inhibition of the phospholipase C gamma 1 hydrolysis [14].…”
Section: Region-specific Transcriptional Response To Chronic Nicotinementioning
confidence: 99%
“…Colorectal cancer patients suffer from various forms of psychological stress reflected in elevated plasma catecholamines levels [7], and it has been shown that HT-29 human colon carcinoma cells, as well as other cancer cells, express α7-nicotinic acetylcholine receptor (α7-nAChR), catecholamine-synthesizing enzymes (tyrosine hydroxylase (TH), and DOPA decarboxylase (DDC), dopamine-β-hydroxylase (DβH), phenylethanolamine N-methyltransferase (PNMT) and adrenergic receptors [8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Through the activated ionic channels or due to the membrane depolarization, Ca 2+ can enter the cells and favour activation (i.e., phosphorylation) of the transcription factor CREB (cAMP response element-binding protein), which in turn modifies gene expression [10,12,13]. Scheme 1.…”
Section: Introductionmentioning
confidence: 99%